The Adolescent Relational Dialectic and the Peer Roots of Adult Social Functioning - Allen, Joseph P. (2013)
The long-term import of a fundamental challenge of adolescent social development—establishing oneself as a desirable peer companion while avoiding problematic behaviors often supported within peer groups—was examined in a community sample of 184 adolescents, followed from ages 13 to 23, along with parents, peers, and romantic partners. The dialectical nature of this challenge appeared in findings that autonomy vis-a-vis peer influences predicted both long-term success avoiding problematic behavior, but also more difficulty establishing strong adult friendships. Conversely, being a desirable peer companion in adolescence predicted more positive adult relationships, but also greater alcohol use. Adolescents who established themselves as both desirable companions and as autonomous vis-à-vis peers were rated as most successful by their parents at age 23.